SPIRITUAL LEADERSHIP BEHAVIOR OF PASTORS AT MINAHASA CONFERENCE, INDONESIA - Lumingkewas, Edwin Melky (Klabat Theological Review, 2021)
Spiritual leadership has become a growing interest among Christians. In the Seventh-day Adventist Church, Fowler (1982) indicates that the problem of pastors‟ work motivation has demanded a deep concern from the worldwide church leadership. In the context of Minahasa Conference (MC), it seems that there is a decline in pastors‟ work motivation that affects the growth of the church. Thus, this study examines the influence of spiritual leadership behavior to pastors‟ work motivation. Using a descriptive design, all 77 pastors at MC were selected as the respondents of the study. In particular, this study determined (a) the biblical-theological foundation of spiritual leadership behavior; (b) the level of spiritual leadership behavior of MC leaders. Using descriptive statistics, the result shows that all the dimensions of spiritual leadership behavior of MC leaders have a high. Keywords: Leadership, Behavior, Pastors